MicrosimUC: Validation of a Low-Cost, Portable, Do-It-Yourself Microsurgery Training Kit - Navia, Alfonso; Tejos, Rodrigo; Canahuate, Sebastian; Machuca, Eduardo; Searle, Susana; Cuadra, Alvaro; Dagnino, Bruno (Journal of Reconstructive Microsurgery, 2021)
Background Microsurgery depends largely on simulated training to acquire skills. Courses offered worldwide are usually short and intensive and depend on a physical laboratory. Our objective was to develop and validate a portable, low-cost microsurgery training kit.Methods We modified a miniature microscope. Twenty general surgery residents were selected and divided into two groups: (1) home-based training with the portable microscope (MicrosimUC, n = 10) and (2) the traditional validated microsurgery course at our laboratory (MicroLab, n = 10). Before the intervention, they were assessed making an end-to-end anastomosis in a chicken wing artery. Then, each member of the MicrosimUC group took a portable kit for remote skill training and completed an eight-session curriculum. The laboratory group was trained at the laboratory. After completion of training, they were all reassessed. Pre- and posttraining procedures were recorded and rated by two blind experts using time, basic, and specific scales. Wilcoxon's and Mann–Whitney tests were used to compare scores. The model was tested by experts (n = 10) and a survey was applied to evaluate face and content validity.Results MicrosimUC residents significantly improved their median performance scores after completion of training (p < 0.05), with no significant differences compared with the MicroLab group. The model was rated very useful for acquiring skills with 100% of experts considering it for training. Each kit had a cost of U.S. $92, excluding shipping expenses.Conclusion We developed a low-cost, portable microsurgical training kit and curriculum with significant acquisition of skills in a group of residents, comparable to a formal microsurgery course.
Keywords: microsurgery; training; low cost; portable; validation